ENGLISH TRANSLATION OF GOD’S PRONOUNS “I”, “HE”, AND “WE” IN (IN)DIRECT SPEECHES IN HOLY QURAN - Junaedi Setiyono (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2017)
The problems are the fact that We, I, and He are all used to represent God in the Holy Quran translated in English, the fact that You does not always refer to the Prophet, and the possibility to use the Direct and Indirect speeches to answer the problems having mentioned. The problems arise because the researcher was informed that the only human being who God speaks directly to him is Moses. Thus, in the Holy Quran, there should not be found We or I because We or I implies that God speaks directly to the Prophet. After the researcher investigates one the longest sura namely Baqara or the Heifer, he finds that the third singular pronoun for God He with all of its derivations (Him and His) appears 85 times, the first plural pronoun for God We with all of its derivations (Our, Ours, and Us) appears 19 times.